Gender And Turn Taking in Mata Najwa Talk Show: A Conversation Analysis - Salma Azzahidah; Evynurul Laily Zen; Evi Eliyanah (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to examine the turn-taking strategy for the same gender and mixed gender that occurred in the Mata Najwa Talk show, as well as to find out the gender pattern that is formed in Indonesia. The data were analyzed using the Have theory (2007) for the turn-taking strategy and Setiawan (2013) for gender patterns that occur in Indonesia. The findings demonstrate that: (1) In the same gender conversation, domination by certain party is rarely found. However, women when talking to their fellow women tend to use more turn-taking strategies in a conversation such as speak then ask, phrases of agreeing and disagreeing, phrases for asking for/giving opinions, and fillers of pauses. Meanwhile, when men talk to other men, the greatest value occurs in the phrase for asking for/giving opinions strategy. (2) In mixed gender conversation, it was found that when women talk to men, men are likely to dominate the conversation. Najwa Shihab as the presenter got less number of turn-taking than men in the strategy of using conjunctions, phrases of agreeing and disagreeing, and phrases for asking for/giving opinions. (3) This research also shows a pattern that occurs in Indonesia, which in this pattern shows that men tend to dominate when talking to women, and this rooted in the dominant gender construction in Indonesia.